Does social influence turn pessimistic consumers green?. (26th March 2021) - Sadiq, Mohd; Adil, Mohd; Paul, Justin
Abstract: The current research investigates the role of social influence on pessimistic consumers' approach toward organic food consumption using the self‐focused regulations theoretical framework. It also examines the mediating and moderating role of environmental concern and social influence on the proposed relationships, respectively. An e‐survey was conducted on 300 Indian consumers. The findings reveal that pessimistic consumers do not typically consume organic food. However, they have a strong concern for the environment, which, in turn, is likely to change them into optimistic consumers who begin to consume organic foods. Further, social influence significantly motivates pessimistic consumers to adopt organic foods and reduces the concern‐behavior gap. The study provides significant implications for organic food marketers and retailers.